Women in Resistance: Relatando o impacto da exposição do IEEE WiEUFRN na Semana de Ciência e Tecnologia da UFRN - Pereira, Monica; Abreu, Marjory (Anais do Women in Information Technology (WIT); 2019: Anais do XIII Women in Information Technology, 2019)
In celebration of the 60th anniversary of UFRN, we have proposed an initiative by IEEE WiEUFRNat CIENTEC aiming to highlight the female contribution to the STEM (Science, Technology, Engineering and Maths) degrees at UFRNover the last 60 years. The highlights were made through an exhibition, composed of four parts: I) description of renowned female icons and their contributions to the STEM areas. II) History of female participation in STEM courses at UFRN, through graphs showing the percentage of female students in the courses since its creation. III) #euexisto campaign: display of testimonials videos from current students of STEM courses explaining why they chose the course. IV) Tribute to female Lecturers: display all female lecturers names that have taught in STEM courses at UFRN. As a result, the group paid a tribute to those brilliant women and highlighted their contribution to STEM; acknowledged the current students and teachers of the courses; and helped raising awareness about the need to encourage the participation of women in these courses and in order to build a more diverse environment. Our main goal was raise awareness that the degrees of STEM had consistently less women than man and thus, our feminist group had a very important role to play in increasing those numbers. From the informal feedback we received, we believe our goal was achieved.